Correlates of cultural adjustment among third culture children in a military setting in the Philippines - Pointon, Barbara Ann Butts 1937-
The study aimed to discover possible relationships among demographic data, personality traits, and cultural adjustment patterns and interpersonal attitudes of selected American military dependent students living overseas, particularly at Clark Air Base. It used comparative and correlational types of statistical treatment to obtain pertinent information on the demographic and personality correlates of the adjustment of overseas American children of Clark Air Base. Based on the results of the study, there should be administrative action on the part of the Wagner Middle and High School heads to help the overseas children adapt their personal and social skills to the new environment and thus, prevent their depressed state, as proven by the result of the California Test of Personality.